Mental Health Visits Among Physicians in their Early Career in Ontario, Canada: Observational Retrospective Cohort Study - Syed, Sarah (Université d'Ottawa / University of Ottawa, 2025)
Background: Physician mental health is an emerging concern within the medical profession. This study focused on examining sex-based differences in mental health visits among early-career physicians compared to non-physicians. Methods: This retrospective, population-based study was conducted using linked administrative data from Ontario, Canada, from April 1, 2004, to March 31, 2018. Results: Among 10,925 early-career physicians, 19.0% had an outpatient mental health visit. Female physicians were found to be at a higher risk for mental health visits compared to male physicians (23.0%vs.15.0%; adjusted hazard ratio [HR] 1.44; 95% CI, 1.35-1.54). However, early-career physicians, regardless of their sex, had a lower likelihood of mental health visits when compared to non-physicians (female physicians: [HR] 0.89; male physicians: [HR] 0.81). Conclusion: Mental health visits are common among females regardless of their physician status. While early-career physicians experience a higher risk of mental health visits, this risk is relatively lower than the matched non-physicians.
Keywords: Physicians; Mental health; Non-physicians; Mental wellbeing; Early career; Ontario